2002
DOI: 10.1002/art.10193
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis in MRL/lpr mice is under the control of multiple gene loci with an allelic combination derived from the original inbred strains

Abstract: Objective. To clarify the mode of inheritance and the genome origins of arthritis in a lupus-prone strain of mice, MRL/MpJ, bearing a Fas deletion mutant gene, lpr (MRL/lpr).Methods. Using non-lupus-prone strains of mice, C3H/HeJ-lpr/lpr (C3H/lpr), (MRL/lpr ؋ C3H/lpr)F 1 intercross and MRL/lpr ؋ (MRL/lpr ؋ C3H/lpr)F 1 backcross mice were prepared. Arthritis in individual mice was analyzed by histopathologic grading, and the genomic DNA of the backcross mice was examined by simple sequence-length polymorphism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 27 publications
4
35
0
1
Order By: Relevance
“…To accomplish this, we and others mapped lupus-predisposing loci in F2 or N2 crosses of MRL-Fas lpr with several other strains, including CAST/Ei (2), C3H-Fas lpr (3)(4)(5)(6), and B6-Fas lpr (where B6 represents C57BL/6) (7). At least 15 loci located on eight of the 19 autosomal chromosomes were identified linked to various lupus-related manifestations.…”
mentioning
confidence: 99%
“…To accomplish this, we and others mapped lupus-predisposing loci in F2 or N2 crosses of MRL-Fas lpr with several other strains, including CAST/Ei (2), C3H-Fas lpr (3)(4)(5)(6), and B6-Fas lpr (where B6 represents C57BL/6) (7). At least 15 loci located on eight of the 19 autosomal chromosomes were identified linked to various lupus-related manifestations.…”
mentioning
confidence: 99%
“…enitis, and arthritis, were genetically segregated by the allelic combinations of these loci (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…5). A previous study (Kamogawa et al 2002) suggested that arthritis in MRL/lpr mice is under the control of multiple gene loci with an allelic combination derived from the original inbred strains by chromosomal mapping of the susceptibility loci to arthritis by using the backcross progeny of MRL/lpr × (MRL/lpr × C3H/lpr) F1 mice. The present results verified this proposed concept more clearly by using RI strains on the ground of the reason as described below.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions, including the calcaneus bone and anterior and posterior synovial tissue at the ankle joints, were evaluated histopathologically. To evaluate the severity of synovitis, the following grading was used: normal, grade 0; thickening and proliferation of synovial lining, grade 1; and grade 1 with granulomatous and/or fibrous lesions in synovial sublining tissue, grade 2 (Kamogawa et al 2002). Pannus formation was categorized as follows: normal, grade 0, extending to bone cortex, grade 1; and further to bone marrow, grade 2.…”
Section: Histopathology Of Arthritismentioning
confidence: 99%
See 1 more Smart Citation